Novel mutation in FBN1 causes ectopia lentis and varicose great saphenous vein in one Chinese autosomal dominant family - Fu, Qing (Molecular Vision, 2014)
PURPOSE: To identify genetic defects in a Chinese family with ectopia lentis (EL) and varicose great saphenous vein (GSV) and to analyze the correlations between phenotype and genotype. METHODS: Twenty-two (12 affected subjects and ten unaffected subjects) among 53 members of a Chinese family underwent complete physical, ophthalmic, and cardiovascular examinations. Genomic DNA was extracted from the leukocytes in the subjects’ peripheral blood. A minimum interval was achieved with linkage study and haplotype analysis. All 65 exons and the flanking intronic regions of fibrillin-1 (FBN1) were amplified with PCR and screened for mutations with direct Sanger sequencing. Molecular modeling was analyzed in an in silico study. RESULTS: The linkage study showed a strong cosegregation signal on chromosome 15. The non-parametric linkage analysis yielded a maximum score of 29.1(p<0.00001), and the parametric logarithm of the odds (LOD) score was 3.6. The minimum interval of the shared haplotype was rs1565863-rs877228. The best candidate gene in this region was FBN1. A novel mutation, c.3928G>A, p.1310G>S in exon 31, was identified in FBN1 and cosegregated well in the family. We applied molecular modeling to show the effect of this mutation on the fibrillin-1 structure. The mutation significantly distorts the calcium coordination, decreases the binding of the calcium ion in that motif, and affects the local calcium-binding epidermal growth factor (cbEGF) interface that depends on Ca binding. CONCLUSIONS: FBN1-associated fibrillinopathies are a group of diseases with dynamic phenotype changes. Novel mutation p.1310G>S was first reported to cause Marfan syndrome (MFS). Our results expand the mutation spectrum in FBN1 and enhance our knowledge of genotype–phenotype correlations underlying FBN1 mutations.